Comparison of cone beam computed tomography and digital radiography in detection of pulpal exposure in external cervical root resorption - Amineh Ghaznavy; Ahmad Reza Talaeipour; Mehdi Vatanpour; Amir Abbas Moshari (Tehran University of Medical Sciences, 2021)
Background and Aims: Pulpal exposures originated from the external cervical root resorptions have major effects on the treatment and prognosis. Therefore, the aim of this study was performed to compare the two different imaging systems-digital radiography with PSP (Photostimulable Phosphor) sensor in three horizontal different views and CBCT (cone beam computed tomography) images to assess the pulpal exposure in simulated cavity of external cervical root resorptions that was performed in 1398 in the School of Dentistry of Azad University. Materials and Methods: 40 intact maxilla anterior teeth with straight roots were included. Teeth were randomly divided to two groups (20 teeth with and 20 without pulpal exposures). Each sample was assessed using PSP digital radiography (in 3 horizontal angles) and CBCT image system, to detect the presence of pulpal exposures. False negative and false positive results in 2 imaging procedures were judged with ratio test. Results: The results showed in CBCT (P.P.V=85.7%) and (N.P.V=89.5%), and in digital intraoral radiography (P.P.V=80%) and (N.P.V=80%) in proximal defects. Ratio test showed that there were no significant differences in the proximal defects (P<0.4). Conclusion: The results showed that there were no significant differences in detection of exposure in the proximal surfaces between two imaging systems.